Framing of local media in the management issues of Sultan Ground and Pakualaman Ground in Yogyakarta - Gilang Jiwana Adikara (Journal of Social Studies (JSS), 2022)
The land management regulations under Law No.13/2002 on the Privilege of Yogyakarta (Privileged Law/UUK) which were fully handed over to the Ngayogyakarta Hadiningrat Sultanate received the spotlight after the publication of a series of investigative reports that revealed allegations of land maladministration in Special Region of Yogyakarta (DIY). However, this disclosure was carried out by the national mass media and did not involve the local mass media. This study reveals how the local mass media during the period 2021-2022 reported on the Ngayogyakarta Hadiningrat Sultanate and its relation to land conflicts in DIY by using the framing method with the Entman method approach. This study concludes that the three mass media in DIY, Kedaulatan Rakyat, Tribun Jogja, and Harian Jogja image that the Ngayogyakarta Hadiningrat Sultanate has properly managed and utilized land rights obtained through the mandate of the Privileges Law for the benefit of the general public.